Challenges and Threats of Over the Counter Dispensing of Medical Termination of Pregnancy Pills: A Review (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Introduction of menstrual regulation with medication (MRM) is a revolutionary advancement towards reducing unsafe abortion and related complications. A systematic literature search was conducted using Google scholar, Pubmed and science direct. Search terms included MTP, unsafe abortion, Misoprostol, self-medication, over the counter, menstrual regulation, pharmacy worker, complication. Studies were limited to the English language. MRM is safe and effective if carried out under medical supervision. Unsupervised over the counter use is associated with many complications like excess bleeding, incomplete abortion, ruptured ectopic, rupture uterus. Although there are well defined guidelines for dispensing MRM pills often those are not followed. Over the counter availability of the drug and self-medication deprive women of accurate information, correct dosage and necessary referral. Proper training of pharmacy dwellers on MRM dosage, eligibility, complications, and referral criteria is necessary. At the same time restriction of over-the-counter dispensing of MRM is current demand of time.Bangladesh J Obstet Gynaecol, 2024; Vol. 39(2): 111-116